PEMBELAJARAN SEKOLAH UNGGULAN DI MASA PANDEMI COVID-19 Studi Tentang Manajemen Pembelajaran di Sekolah Menengah Atas Islam Terpadu Hidayah Klaten - Kelik Wardiyono; Siti Choiriyah; Wasis Pambudi (STAI Masjid Syuhada Yogyakarta, 2021)
Covid-19 brings implications in various aspects of life for the world community, one of which is education. Schools in Indonesia